Frequency analysis of symptomatic worsening following ketamine infusions for treatment resistant depression in a real-world sample: Results from the canadian rapid treatment center of excellence. (January 2022) - Di Vincenzo, Joshua D.; Lipsitz, Orly; Rodrigues, Nelson B.; Jones, Brett D.M.; Gill, Hartej; Lee, Yena; Lui, Leanna M.W.; Teopiz, Kayla M.; Ho, Roger; Lin, Kangguang; Nasri, Flora; McIntyre, Roger S.; et al.
Abstract: Antidepressants are associated with symptomatic worsening in a subgroup of patients. Replicated evidence has demonstrated rapid and robust antidepressant effects with intravenous (IV) ketamine in treatment resistant depression (TRD); however, the risk of ketamine worsening depressive symptoms in a subgroup of patients remains unknown. Herein we report a retrospective analysis on the rates of symptomatic worsening during an acute course of IV ketamine in individuals with unipolar ( n  = 142) and bipolar ( n  = 22) TRD. Adults ( N  = 164; mean age = 45.97) with TRD underwent four sub-anesthetic infusions (0.5–0.75 mg/kg over 40 min) of IV ketamine over two weeks, and were assessed with the Quick Inventory for Depression Symptomatology-Self Report-16 (QIDS-SR16 ) at baseline and after each infusion. The primary outcome was the proportion of patients experiencing clinically significant worsening of depressive symptoms (≥20% increase on the QIDS-SR16 ) at each time point relative to baseline. Secondary analyses explored trends in the results. The frequency of clinically significant worsening fluctuated between 1.83% to 5.49%, with no identifiable trend across time. Zero individuals with bipolar TRD reported symptomatic worsening. Limitations include the single-centered, uncontrolled, retrospective nature of this study. Rates of symptomatic worsening associated with IV ketamine therapy for TRD appear to be very low and similar to conventional antidepressants.